Undergraduate students' perceived academic environmental characteristics as correlates of learning outcomes (2004)
This study examined the relationship between undergraduates' perception of the academic environment, their attitude to academic work and achievement. A total of 348 undergraduates who formed the sample were drawn from five departments in three universities in Nigeria. The study revealed that four dimensions of the academic environment as perceived by students, seemed to be potent factors influencing students' attitude to academic work. These perceived factors were: commitment of lecturers to teaching and committment expected of students; personal attention given to students; academic guidance and respect for students. Two other dimensions - freedom in students' learning and the relationship with students correlated significantly with only one dimension of attitude to academic work respectively. However, students' GPA correlated negatively with two dimensions of academic environment- academic guidance and personal attention given to students. The implications for teaching and learning in Nigerian tertiary institutions were discussed.